Population growth and the problem of un-employment - Gupta, S. P. (New Delhi : Anmol Publications, 1990)
Population Is The Vital Component In The Process Of Socio-Economic Development In A Country. The Level Of Welfare And The Improvement In The Quality Of Life Of People Are Related To The Management Of Population By A Government. If Population Is Allowed To Take Its Natural Course In An Underdeveloped Country Like India, It Is Apt To Weaken The Very Fabric Of Economic System.This Treatise Seeks To Highlight The Trend Of Population Growth, The Efforts Made By The Government In The Form Of Family Welfare Programme And The Trend Of Unemployment Existing In The Country. Efforts Have Also Been Made To Project A Level Of Unemployment By 1991, Unless The Strategy Adopted By The Government To Check Population Growth Is Transformed Completely.Suggestions Have Also Been Made To Enforce Changes In The Government Policy So That The Incidence Of Unemployment Could Be Reduced In The Larger Interest Of The Country.
Includes bibliographical references
Keywords: Birth control -- India -- Jammu and Kashmir; Unemployment -- India -- Jammu and Kashmir